2014
DOI: 10.1007/s10464-014-9679-6
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Women's Aggression Against Partners and Others: Broadening Our Understanding of Violence

Abstract: Research on women's aggression typically focuses on relational aggression. However, the study of violence must include multiple forms of violence such as aggression against partners and non-partner others, while also considering victimization experiences by partners and non-partners. The focus of this study is the multiple experiences of violence (perpetration and victimization) of women who are incarcerated. Incarcerated women are likely to experience higher rates of both than women in community settings, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Research on both women in prison and prospective studies of individuals maltreated as children support a link between childhood abuse and women’s violence. For incarcerated women in several states (Texas, Michigan, and Oklahoma), histories of childhood and adult victimization were related to their violence in the community (Byrd & Davis, 2009; McClellan, Farabee, & Crouch, 1997; Rivera, Kubiak, & Bybee, 2014). Also, women in federal prison in 1991 and 1997 with more serious abuse histories acted more violently than others while they were incarcerated (Steiner & Wooldredge, 2009).…”
Section: The Nature Of Violence By Womenmentioning
confidence: 99%
“…Research on both women in prison and prospective studies of individuals maltreated as children support a link between childhood abuse and women’s violence. For incarcerated women in several states (Texas, Michigan, and Oklahoma), histories of childhood and adult victimization were related to their violence in the community (Byrd & Davis, 2009; McClellan, Farabee, & Crouch, 1997; Rivera, Kubiak, & Bybee, 2014). Also, women in federal prison in 1991 and 1997 with more serious abuse histories acted more violently than others while they were incarcerated (Steiner & Wooldredge, 2009).…”
Section: The Nature Of Violence By Womenmentioning
confidence: 99%
“…ACEs have been shown to increase the risk of women’s IPV both directly and indirectly (Allen et al, 2009 ; Kubiak et al, 2017 ; Dowd et al, 2005 ; Kernsmith, 2006 ; Rivera et al, 2014 ; Siegel & Williams, 2003 ; Sullivan et al, 2005 ). Kruttschnitt et al ( 2002 ) found a direct correlation between childhood physical abuse and adult female perpetrated IPV.…”
Section: Introductionmentioning
confidence: 99%
“…However, IPV and victimization during the life course are not isolated incidents in women’s lives. Often victimization becomes a pattern for women, occurring in childhood, repeated from relationship to relationship, and then a contributing factor to the use of aggression toward partners and others (Kubiak et al, 2017; Rivera et al, 2014; Saxena & Messina, accepted ).…”
Section: Introductionmentioning
confidence: 99%